Penerapan Pembelajaran Psikologi Warna untuk Meningkatkan Kemampuan Mahasiswa Dalam Memilih Warna pada Desain Kemasan Produk Prodi Manajemen FEB UNISMA - Eka Farida; Neneng Rika Jazilatul Kholidah; Sarjono Sarjono (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2020)
Provide  Color is the fastest method of delivering messange and meaning in the non-verbal communication category. The use of color in packaging design is very important. Good product packaging requirements are as a place, attractive, can protect, practical, cause self-esteem, accuracy of size, and transportation. Color selection decisions on student product packaging design can be analyzed from color psychology. The purpose of this study is to analyze the application of color psychology learning to improve students ability in color selection in product packaging design. The research includes an assessment of the understanding of color psycology and the ability to choose colors that are implemented in product packaging design. Total population and sample of 30 respondents with saturated sampling technique. The method used in this research is experimental and ex-post facto explanatory nature. Data collection techniques using questionnaires, observations, evaluation result (score), and interviews. Data analysis using descriptive qualitative analysis and t test. The result showed satisfactory understanding of the color psychology of students, the suitability of product packaging design with color psycology, packaging design assesment is very good and good. The  effectiveness test of the application of color psychology learning to the color selection ability in packaging design by 56,2%.